The complex globular cluster system of the S0 galaxy NGC 4382 in the outskirts of the Virgo Cluster. Issue 1 (8th January 2022) - Escudero, Carlos G; Cortesi, Arianna; Faifer, Favio R; Sesto, Leandro A; Smith Castelli, Analía V; Johnston, Evelyn J; Reynaldi, Victoria; Chies-Santos, Ana L; Salinas, Ricardo; Menéndez-Delmestre, Karín; Gonçalves, Thiago S; Grossi, Marco; et al.
ABSTRACT: NGC 4382 is a merger-remnant galaxy that has been classified as morphological type E2, S0, and even Sa. In this work, we performed a photometric and spectroscopic analysis of the globular cluster (GC) system of this peculiar galaxy in order to provide additional information about its history. We used a combination of photometric data in different filters, and multiobject and long-slit spectroscopic data obtained using the Gemini/GMOS instrument. The photometric analysis of the GC system, using the Gaussian Mixture Model algorithm in the colour plane, reveals a complex colour distribution within R gal < 5 arcmin (26.1 kpc), showing four different groups: the typical blue and red subpopulations, a group with intermediate colours, and the fourth group towards even redder colours. From the spectroscopic analysis of 47 GCs, confirmed members of NGC 4382 based on radial velocities, we verified 3 of the 4 photometric groups from the analysis of their stellar populations using the ULySS code. NGC 4382 presents the classic blue (10.4 ± 2.8 Gyr, [Fe/H] = −1.48 ± 0.18 dex), and red (12.1 ± 2.3 Gyr, [Fe/H] = −0.64 ± 0.26 dex) GCs formed earlier in the lifetime of the galaxy, and a third group of young GCs (2.2 ± 0.9 Gyr; [Fe/H] = −0.05 ± 0.28 dex). Finally, analysis of long-slit data of the galaxy reveals a luminosity-weighted mean age for the stellar population of ∼2.7 Gyr, and an increasing metallicity from [Fe/H] = −0.1 to +0.2 dex in R gal < 10 arcsec (0.87 kpc). These values, and other morphological signatures in the galaxy, are in good agreement with the younger group of GCs, indicating a common origin as a result of a recent merger.